Analisis kondisi sanitasi masyarakat pinggir sungai dengan pendekatan studi EHRA di Kelurahan Tembilahan Kota - Ahmad Faisal; Zulfan Saam; Elda Nariati (Jurnal Zona, 2017)
Indragiri Hilir is low lan areas or riverbank is swamp, which has a many rivers and stream. Riverbank area there are many settlements with spesific conditions of sanitation facillities,This study uses the method of approach through studies EHRA by conducting explorative survey to look at the household scale sanitary conditions. variable research is a sanitary garbage , latrines , household waste and clean water. Sampling technique using a random sampling of the population of people who live on the riverbank with the inclusion criteria of 493 households , obtained a sample of 125 housewives. The results showed that the sanitary conditions of communities riverbank in the village Tembilahan cities include: community do not do waste treatment and immediately throw it into the river , sanitary latrines still use the river as a defecation , people immediately dispose of household waste into the river , meeting the needs of clean water to eat and drink is obtained from sources rainwater as well as for bathing and washing using river water. Communities riverbank in the village Tembilahan cities categorized as moderate risk areas . public sanitation on communities riverbank in the village Tembilahan cities do not have basic sanitation standards and the need for a proper settlement.